PSYCHOEDUCATION AND THE DIABETES T-PLATE MODEL AS A STRATEGY TO IMPROVE SELF-CARE BEHAVIOR IN PEOPLE WITH DIABETES MELLITUS - Minarti Minarti; Rini Ambarwati; Ach. Arfan Adinata (Universitas Airlangga, 2026)
Diabetes Mellitus (DM) is a chronic disease requiring long-term management, particularly through appropriate dietary management. However, the low knowledge of DM sufferers regarding healthy dietary principles results in suboptimal self-care behavior and increases the risk of complications. This condition was also found in the Prolanis Diabetes Mellitus group at the Tambakrejo Community Health Center, Surabaya. This community service activity aims to improve the knowledge, skills, and self-care behavior of DM sufferers through psychoeducation-based education and training using the Diabetes T Plate Model. The activity was carried out in two meetings (approximately 120 minutes per meeting) on ​​June 28 and July 10, 2025, involving 25 DM sufferers. Evaluation was carried out through a pre-test and post-test using a questionnaire that assesses knowledge and an observation sheet to assess the implementation of the T Piringku diet. The results showed a significant increase in participant knowledge, with the lowest score increasing from 40 to 73 and the average post-test being higher than the pre-test. All participants were included in the very successful category in practicing the diet, showing interest in implementing the Diabetes T Plate guidelines, although some still habitually consume high-fat foods. Thus, psychoeducation-based education using the Diabetes T-Plate Model effectively improves knowledge and self-care skills in people with diabetes. This intervention has the potential to support glycemic control and complication prevention and can be replicated in community programs with family support and ongoing follow-up.